Effects of Si solute on the glass formation and atomic structure of Pd liquid. (4th February 2019) - Yang, Z J; Tang, L; Wen, T Q; Ho, K M; Wang, C Z
Abstract: Molecular dynamics simulations were performed to study the effects of Si solute on the glass formation and crystallization of Pd liquid. Pure Pd samples prepared by a quenching process with a cooling rate of 10 13 K s −1 can be in an amorphous state but the structural analysis indicates there is nearly no glass-forming motif in the sample. However, doping a small amount of Si (Si concentration ~4%) the sample can be vitrified at a cooling rate of 10 12 K s −1 . The glass-forming motifs such as Pd-centered Z 13, Si-centered Z 9-like and mixed-ICO-cube clusters with five-fold local symmetry are found to be the dominant short-range orders in the glassy samples. With the increasing of the Si-doping concentration, these glass-forming motifs tend to aggregate and connect with each other forming a network structure. Our calculated results revealed that Si solutes in liquid Pd can significantly enhance the glass-forming ability.